First Line Anti-Tubercular Drug Resistance Pattern of Mycobacterium Tuberculosis Isolated From Specialized Hospitals of Dhaka City - Mohiuddin, Md; Haq, J Ashraful (Ibrahim Medical College Journal, 2016)
The present study was undertaken to determine the drug resistance pattern of M. tuberculosis isolated from 225 pulmonary and 45 extrapulmonary tuberculosis cases. The samples were cultured on Lowenstein Jensen (L-J) media for isolation of M. tuberculosis. Drug resistance to first line anti tubercular drugsnamely isoniazid (INH), rifampicin (RIF), Ethambutol (ETH) and streptomycin (SM) were determined by indirect proportion method. The overall drug resistance of M. tuberculosis was 53.6% to any of the first line anti tubercular drugs. Rate of multi drug resistant tuberculosis (MDR-TB) among the untreated cases was 4.2%, while it was 36.0% in previously treated cases. It was found that 83.3% rifampicin resistant M. tuberculosis was cross resistant to one or more of other first line anti-tubercular drugs, while cross resistance of INH, ETH and SM resistant isolates was much low. The present study revealed that high level of drug resistance exists to individual anti tubercular drugs and MDR-TB is an emerging problem, particularly in treated cases. Rifampicin resistance could be used as a surrogate marker for drug resistance to other first line anti tubercular drugs. Ibrahim Med. Coll. J. 2014; 8(2): 41-46